Penerapan dan Pengendalian Jaringan Komunikasi pada Sistem Informasi Akuntansi Berbasis Komputer - Nung Harjanto (Journal of Accounting and Investment, 2002)
The information system has a strategic position for the company to achieve organizational goals. With the support of computer technology, the information generated will be presented with an accurate, secure and fast. Organizational information system is designed such that it can support the organization's operations and decision making. With the network system, each organizational unit are connected to one another in a local, regional and even multinationals that transfer of information can take place quickly and easily so as to encourage high efficiency. Besides, information technology can send information in various forms (data, visual, and audio-visual). The communication network can be constructed through three organizational approaches, a) centralized network, b) decentralized system and c) distributede of data processing. Each of these approaches has advantages and disadvantages. Besides, there are advantages and disadvantages of computer-based information system has some potential threats, such as vulnerability to loss or corruption of data, the difficulty of the data to be searched, and computer crime. The designers of information systems as well as top managers are encouraged to consider these matters so that the application of computer-based accounting information system can be completely managed and controlled so safe and beneficial in supporting the activities of the company.